2023
DOI: 10.1021/acs.chemmater.3c01232
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Micropower Harvester from Supramolecular Assembly of Chiral Ambipolar Chromophores

Swadesh Paul,
Shubhankar Barman,
Aritri Pal
et al.

Abstract: This Article reveals highly promising piezoelectricity in chiral supramolecular assemblies of trialoxybenzamide-functionalized acceptor−donor−acceptor (ADA)-type ambipolar π-systems. In the three conjugated molecules (AD 1 A, AD 2 A, and AD 3 A), naphthalimide and thiophene units represent A and D, respectively, while the number of conjugated thiophene units is indicated by the number in the subscript. These systems exhibit helical supramolecular polymerization in hydrocarbon solvents, producing a fibrillar ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Recently, we have shown that the FE hydrogen-bonded supramolecular polymers of ADA-type ambipolar π-systems, when cast into flexible device structures, could be useful for a sensitive piezo biosensor to monitor wrist pulses stimulated by normal human physiological action. [81] Cascade D-A organic FE layers, between graphene sheets, were theoretically predicted for application in solar cells. The functionality of the presented system was compared to that of integrated heterojunctions, in which the addition of the electron and hole transport layers was shown not to be necessary for electron and hole transport across the layers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have shown that the FE hydrogen-bonded supramolecular polymers of ADA-type ambipolar π-systems, when cast into flexible device structures, could be useful for a sensitive piezo biosensor to monitor wrist pulses stimulated by normal human physiological action. [81] Cascade D-A organic FE layers, between graphene sheets, were theoretically predicted for application in solar cells. The functionality of the presented system was compared to that of integrated heterojunctions, in which the addition of the electron and hole transport layers was shown not to be necessary for electron and hole transport across the layers.…”
Section: Discussionmentioning
confidence: 99%
“…Further, they demonstrated a self‐powered biomedical sensor from the device to monitor physiological signal monitoring. Recently, we have shown that the FE hydrogen‐bonded supramolecular polymers of ADA‐type ambipolar π‐systems, when cast into flexible device structures, could be useful for a sensitive piezo biosensor to monitor wrist pulses stimulated by normal human physiological action [81] . Cascade D‐A organic FE layers, between graphene sheets, were theoretically predicted for application in solar cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the research group of Stupp studied an amphiphilic oligopeptide tethered with an ONB photo-protecting group (32) in the junction of the alkyl chain and peptide segment (Fig. 15).…”
Section: Morphology Regulation By Photo-initiated Group Cleavagementioning
confidence: 99%
“…Subsequently, it is possible to externally regulate the efficacy of a biologically active motif using light and the site-specific delivery of payloads is also viable. The morphological changes are often associated with the change in the anisotropy of the resulting sample which impacts the electronic properties including conductivity, 28,29 piezo-response, [30][31][32] etc. and provides the opportunity to fabricate controllable smart materials.…”
Section: Introductionmentioning
confidence: 99%